2000
DOI: 10.1016/s0375-9474(99)00841-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a variational approach to approximate particle number projection with effective forces

Abstract: Kamlah's second order method for approximate particle number projection is applied for the first time to variational calculations with effective forces. High spin states of normal and superdeformed nuclei have been calculated with the finite range density dependent Gogny force for several nuclei. Advantages and drawbacks of the Kamlah second order method as compared to the Lipkin-Nogami recipe are thoroughly discussed. We find that the Lipkin Nogami prescription occasionally may fail to find the right energy m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…As pointed out in Refs. [18][19][20][21], the parabolic approximation, which corresponds to a sum up to the second order of the Lipkin or Kamlah [22] approximation, may fail at the limit of weak pairing. In this work we extend the Lipkin method beyond the second order used so far, so as to make the first tests of its convergence and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out in Refs. [18][19][20][21], the parabolic approximation, which corresponds to a sum up to the second order of the Lipkin or Kamlah [22] approximation, may fail at the limit of weak pairing. In this work we extend the Lipkin method beyond the second order used so far, so as to make the first tests of its convergence and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Applications based on effective nuclear interactions have been particularly successful in the description of super-deformed rotational bands in several regions of the mass table [1][2][3][4][5]. In the cranking method, a rotational band is generated by the rotation of a deformed intrinsic state.…”
Section: Introductionmentioning
confidence: 99%
“…The second order in this expansion takes into account the particle number fluctuations and might cure some of the deficiencies of the first order approximation. However, full calculations up to second order are rather cumbersome [23,8,9] and most second order calculations have been done using the Lipkin-Nogami (LN) recipe proposed in Refs. [10][11][12].…”
mentioning
confidence: 99%
“…This behavior could be associated with a failure of the LN expansion at the phase transitions. As a matter of fact in reference [9] it has been shown that large changes in the h 2 parameter are associated with the breakdown of the second order expansion of the projected energy. On the left hand side of Fig.…”
mentioning
confidence: 99%